Obstacle Avoiding Robot Car - Thakkar, Jayati Anilkumar; Shah, Trusha; Shaikh, Nishat (International Journal of Reconfigurable and Embedded Systems (IJRES), 2021)
This paper proposes a design and implementation of a remote-controlled car run by Bluetooth Technology via an Android device. In this work, hardware and software technologies are used such as Arduino, Motor driver and Bluetooth module. Arduino is an Opensource prototyping platform supported easy-to-use hardware and software. Arduino uses an ATmega328 microcontroller. The objective of this project is to form an omnipresent technology for automobiles that operate in lifestyle with an effective system. In this project, the brain of the robot, Arduino microcontroller is programmed in such a way that it can detect any obstacle in a defined range and can choose a path with no obstacle in between. Since robotics has become a significant part in our standard of living and also within the engineering field and it plays an important role within the development of latest technology, This project can be made in a very bigger scale for real-time vehicles.This paper proposes a design and implementation of a remote-controlled car run by Bluetooth Technology via an Android device. In this work, hardware and software technologies are used such as Arduino, Motor driver and Bluetooth module. Arduino is an Opensource prototyping platform supported easy-to-use hardware and software. Arduino uses an ATmega328 microcontroller. The objective of this project is to form an omnipresent technology for automobiles that operate in lifestyle with an effective system. In this project, the brain of the robot, Arduino microcontroller is programmed in such a way that it can detect any obstacle in a defined range and can choose a path with no obstacle in between. Since robotics has become a significant part in our standard of living and also within the engineering field and it plays an important role within the development of latest technology, This project can be made in a very bigger scale for real-time vehicles.